Litterbug - Science History Institute (2022)
A yellow game box decorated with an illustration of an insect-like character and several children. The box contains 1 game board, instructions, 1 spinner, 4 silver cardboard "litter barrels", and a bag of paper "trash" squares. The object of the game is to keep the community clean and free of litter by collecting "trash" and depositing it in cardboard trash cans. Each player travels around the board collecting litter, then depositing the litter in their trash container. The player who picks up the most litter is the winner.
Keywords: Board games; Environmental protection; Environmental protection--Study and teaching; Litter (Trash)